Duo-bottle / Maybelyna Deborah Dick ... [et al.] - Dick, Maybelyna Deborah; Hamzah, Nurashikin; Henry, Jacqueline; Mohamad Musa, Nurafiqah (2021)
Duo-Bottle is a bottle that can do both heating and cooling process for liquid such as water and other types of drinks. This bottle will be made of plastic polymers such as polypropylene and co-polyester, which makes them light and durable. Heater and cooler system will be placed at the bottom of the bottle. The main aim of this product is to ease the difficulties of heating and cooling water during camping or hiking, as well as to reduce environmental pollution. Novelty of Duo-Bottle is that it uses fingerprint instead of buttons, to switch on or switch off the heater or cooler. Besides that, Duo-Bottle has 2 ways to charge which the first one is using cable (electricity) and second one is using solar power. Traditionally, we need to set up campfire to heat water during camping, which could cause air pollution and reduce the quality of the water. With the existence of Duo-Bottle, we are not only reducing air pollution, but also save power source (electricity usage). As mentioned, Duo-Bottle is chargeable, so consumer can unplug the charger when needed to use it without need to worry about its source of energy because it is also chargeable using solar power.